Longitudinal immune profiling uncovers regulatory T cell signatures associated with the progression of COVID-19 - Kossack, Camila; Bravo, Felipe; Fuentes-Villalobos, Francisco; Quevedo, Claudio; Medina, Matías A.; Riquelme, Raúl; Rioseco, María Luisa; Calvo, Mario; Pino-Lagos, Karina; Aguilera, Felipe; Barría, María Inés; Garrido, José Luis (Frontiers in Immunology, 2025)
IntroductionThe role of Regulatory T cells (Tregs) in severe COVID-19 remains unclear. Some authors reported that Tregs increased in peripheral circulation, while other investigators reported that these cells decreased in severe COVID-19 patients. The expression of FoxP3 in Tregs remains inconsistent and controversial. These observations have been made using immune phenotyping via flow cytometry and T-cell sequencing; however, none of these data provide a clear indication of what Tregs are doing in this chaotic hyperactivated immune response. MethodsWe conducted a comprehensive characterization of the Treg compartment in a longitudinal cohort of patients with acute COVID-19, including individuals with mild or severe disease. Using RNA-seq, we analyzed gene expression across the cohort, while flow cytometry enabled us to determine Treg phenotype and observe changes during disease progression. Furthermore, we assessed Treg activity through a suppression assay. ResultsGene expression analysis revealed significant downregulation of genes involved in regulatory pathways supporting T regs' functional activities, consistent across the severe patients analyzed. In contrast, we found increased expression of these genes in patients with mild disease. This finding was further confirmed by phenotyping analysis, which showed significant differences in CD25+CD127- Treg cells between mild and severe patients, positively associated with CTLA-4 and PD-1 inhibitory markers. Surprisingly, these results did not correlate with FoxP3 expression. Furthermore, a high frequency of CD25+CD127- Treg cells was associated with young, mild patients. In contrast, a lower frequency of CD25+CD127- cells and a higher frequency of FoxP3+ cells were associated with elderly patients. Finally, a Treg functional assay showed a lower capacity for suppression in Tregs obtained from severe patients compared to those from mild patients in the acute phase of the disease. DiscussionOur findings offer critical insights into the role of Tregs in SARS-CoV-2, with implications that extend beyond this viral infection. Understanding how Tregs contribute to immune responses in COVID-19 could inform therapeutic strategies to modulate immune regulation in infectious diseases more broadly.